Importance of the Electrolyte Cation on the Non-Covalent Interactions in the Electrooxidation of 1-Heptanol on Gold in 0.1 M Alkali Metal Hydroxides - Ureta-Zanartu, M; Mascayano-Collado, C; Fernandez-Vidal, F (Elsevier Ltd, 2020)
In order to determine the possible non-covalent influence of the alkali metal cation on the electrooxidation of 1-heptanol on gold in alkali metal hydroxides, 0.1 M MOH solutions, where M = Li, Na, K, Rb, and Cs, have been used. The charge-transfer resistance, determined by Electrochemical Impedance Spectroscopy, of heptanol oxidation at a fixed potential increased monotonically by a factor of 4 from LiOH to RbOH, that is, the heptanol oxidation current decreased. Since the degree of hydration of the OH group of the alcohol, as estimated by Molecular Dynamics Simulation, increased by a factor of 5 from LiOH to RbOH, it can be concluded that the decrease of the heptanol oxidation current from LiOH to RbOH is due to an increasing hydration of the heptanol OH group, which would hinder its access to the electrode surface. This result is in line with the previous finding [M.S. Ureta-Zañartu, C. Mascayano, C. Gutiérrez, doi:10.1016/j.electacta.2015.02.230] that the increase of the alcohol oxidation current at a fixed potential of linear saturated aliphatic alcohols from C1 to C7 on gold, both in a pH 11 buffer and in 0.1 M NaOH, increased with increasing chain length, that is, with decreasing hydration (because of the increasing hydrophobicity) of the alcoholic OH group. © 2020 Elsevier B.V.